The history of family therapy - Gooh, Mo Lee (2015)
To begin with, before taking a closely look at the history of family therapy, I shall bring some explanations of the term “Family Therapy” in terms of its definition, aims, benefits and so on so forth. After that, I will be taking into account both the differences and similarities between family therapy and group counseling at the same time. This can enhance our understanding towards getting into the explanation of the history of family therapy better. By just taking a moment and before jumping in to get to know the meaning of family therapy, the word ‘family’ really caught my attention. Perhaps we can take a moment to find out what defines family first. According to Webster’s Dictionary, family defines as a group of people who are bound by philosophical, religious or other convictions, common ancestry and people who are living under the same roof. Other definition of family would be a basic biosocial unit in society having as its nucleus two or more adults living together and cooperating in the care and rearing of their own or adopted children. Family is also considered as a system in which each member has a significant influence on all other members.